Competitive Intensity as a Quasi-moderator of the Relationship between Innovative Efforts and Performance - Johnny, Johnny (Master of Management, Faculty of Economics and Business, Universitas Gadjah Mada, 2006)
This study empirically investigates the moderating effect of competitive intensity on the relationship between innovative efforts and performance. The study proposes that a firmâs competitive intensity acts as a quasi-moderator of the relationship between innovative efforts and performance.The results support the predictions of the study. The results indicate that competitive intensity moderates the relationship between innovative efforts and performance such that when competitive intensity is high, the relationship between innovative efforts and performance is positive, and vice versa, when the competitive intensity is low, the relationship between innovative efforts and performance is negative. Furthermore, the results reveal that competitive intensity has a positive relationship to the level of innovative efforts but has a negative relationship to performance.